Leadership, Learning, and Psychological Empowerment in Driving Organizational Performance - Vivi Pancasari Kusumawardani; Meiske Claudia; Rini Rahmawati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines how adaptive leadership and organizational learning capability influence organizational performance through psychological empowerment within the context of regional development banking. Addressing a gap in the existing literature, this research integrates organizational culture as a moderating mechanism in the relationship between psychological empowerment and organizational performance, an aspect that has received limited empirical attention, particularly in regional development banks. Data were collected through a survey of 290 employees of PT Bank Pembangunan Daerah Kalimantan Tengah (Bank Kalteng) using purposive sampling and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that adaptive leadership and organizational learning capability positively affect psychological empowerment and organizational performance, while psychological empowerment mediates these relationships. Furthermore, organizational culture significantly moderates the effect of psychological empowerment on organizational performance, highlighting the importance of cultural alignment in translating employee empowerment into performance outcomes. Theoretically, this study contributes by extending leadership and organizational learning research through an integrative framework that incorporates psychological and cultural mechanisms in explaining organizational performance. Practically, the findings offer insights for managers and policymakers in regional development banks to enhance sustainable performance through adaptive leadership, learning-oriented practices, employee empowerment, and supportive organizational cultures. Keywords: adaptive leadership, organizational culture, organizational learning capability, organizational performance, psychological empowerment